TRANSFORMING FINANCIAL SYSTEMS: THE ROLE OF DATA ENGINEERING IN FRAUD DETECTION, RISK MANAGEMENT, AND OPERATIONAL EFFICIENCY - Saurabh Kumar (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive article explores the transformative impact of data engineering on modern financial systems, focusing on critical areas, including fraud detection, risk management, and operational efficiency. The article delves into the evolution of financial technology infrastructure, highlighting how advanced data processing capabilities, machine learning implementations, and robust security frameworks have revolutionized the banking sector. The study investigates key technological advancements in real-time transaction processing, data warehousing solutions, and automated monitoring systems, demonstrating how these innovations have enhanced fraud prevention, regulatory compliance, and overall system reliability. Through a detailed examination of current industry practices and emerging trends, this analysis provides insights into how financial institutions leverage sophisticated data engineering practices to maintain security, ensure compliance, and deliver enhanced customer experiences in an increasingly digital banking landscape.